THE INTEGRATION OF ESG REPORTING IN ACHIEVING SUSTAINABLE ECONOMIC DEVELOPMENT: A GLOBAL LITERATURE REVIEW - Safwan; Almunadiya; Rahmiatul Aula; Raudhatinur; Mauliza Sari (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The growing urgency of sustainable economic transformation has positioned green accounting as a vital mechanism linking corporate behavior to sustainable development. This study aims to explore how green accounting contributes to sustainable economic development through a systematic literature review (SLR) of 85 Scopus-indexed studies published between 2015 and 2024. The analysis integrates perspectives from accounting, management, and development economics to identify theoretical and practical linkages. Findings reveal that green accounting enhances sustainable economic performance by promoting environmental efficiency, resource accountability, and innovation in corporate governance (Mishra et al., 2022). However, challenges such as the absence of uniform reporting standards, limited institutional capacity, and weak regulatory enforcement hinder its full implementation, especially in developing economies (Qian et al., 2022). Furthermore, integrating green fiscal policies and ESG reporting framework strengthens the connection between corporate sustainability and macroeconomic growth (Wang & Li, 2022). This study contributes by bridging disciplinary gaps and offering a conceptual framework that positions green accounting as a catalyst for inclusive, transparent, and sustainable economic growth. It provides practical implications for policymakers and organizations aiming to align financial systems with long-term environmental and developmental goals.